Study on the Clinical Spectrum of Respiratory Conditions Presenting with Hypercapnic Respiratory Failure – A Cross-Sectional Observational Study - Dr kauser mohd Yaseen shaikh; Dr. K. Bhaskar; Dr G.K.Paramjyoth (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Hypercapnic respiratory failure (HRF) reflects failure of pulmonary ventilation and confers substantial short-term morbidity and mortality. Patterns of disease precipitating HRF vary geographically and influence outcome. Methods: We performed a prospective cross-sectional study at a tertiary centre in Hyderabad (Sept 2022 – Feb 2023). Sixty-nine consecutive adults (≥18 y) with respiratory-cause HRF (PaCO₂ > 45 mmHg, pH < 7.35) were enrolled. Clinical variables, comorbidity, arterial blood-gases, radiology, echocardiography and hospital course were recorded. Non-invasive ventilation (NIV) was first-line; failure was defined as need for endotracheal intubation or in-hospital death. Descriptive statistics and logistic regression explored factors associated with NIV failure and mortality. Results: Mean age was 55 ± 16 y; 50.7 % were male. Leading aetiologies were acute exacerbation of COPD (AECOPD, 26 %), bronchiectasis (9 %), and OSA/OHS (7 %); mixed phenotypes accounted for 42 % (Figure 2). Hypertension (39 %) and diabetes (25 %) were common comorbidities. Median hospital stay was 7 days (IQR 6–8). NIV succeeded in 85.5 % (59/69). NIV failure (14.5 %) was strongly associated with prior-year HRF admission (OR 4.3, p = 0.029) and in-hospital mortality (100 % vs 3 %, p < 0.001). Overall mortality was 11.6 %; AECOPD contributed 62.5 % of deaths. Conclusion: In this South-Indian cohort, AECOPD—often co-existing with other airway diseases—was the commonest precipitant of HRF and the principal driver of mortality. NIV was effective in the majority; previous HRF admission heralded NIV failure and death, highlighting a target group for enhanced post-discharge care.